Training, Competition & Health - Steinacker JM; Schellenberg J; Bloch W; Deibert P; Friedmann-Bette B; Grim C; Halle M; Hirschmüller A; 8; Hollander K; Kerling A; Kopp C; et al. (Dynamic Media Sales Verlag, 2022)
Introduction: An infection with SARS-CoV-2 is relevant especially in high-performance sport due to possible organ damage and reduced performance which occurs in individual cases. Various recommendations are found in the literature concerning when safe return to sports is possible and what examinations are suitable to support this decision. The dominance of other virus variants than those at the start of the pandemic makes revision of earlier recommendations necessary. Methods and Analysis: The recommended actions are based on the currently-available scientific knowledge of the pathogenicity of the virus and on clinical experiences in general and elite athletes. Twenty-one recommended actions were proposed by the Scientific Council of the DGSP, discussed and agreed on in consensus with experts from German-language sports-medical facilities and evaluated by an independent co-author. The resultant position paper was subsequently released by mutual agreement. Results: The recommendations are oriented to the severity of the course and the symptoms. The required medical diagnostic is deduced therefrom. During persistent symptoms, sports should be paused and training only begun again at low intensity after a three-day symptom-free period. If COVID-19-associated complaints recur, physical exertion should be stopped and a doctor consulted. After moderate and serious course, medical diagnostics are required prior to the start of training. Summary: To prevent a health risk due to sports and thereby resultant organ damage after a SARS-CoV-2 infection, a procedure adapted to the symptoms and course before return to training and finally to competitive sports is recommended.